Investigation of V2O5-ZnAl2O4 composite nanoparticles for C-band microstrip patch antenna applications - Srilali Siragam; Dr Raghvendra S Dubey; Lakshman Pappula (Kuwait Journal of Science)
This paper reports the prototype fabrication and characterization of microstrip patch antenna using the sol-gel derived composite nanoparticles of vanadium pentoxide oxide (V2O5) and zinc aluminate (ZnAl2O4). The prepared composite nanoparticles were characterized using X-ray diffraction (XRD), which exhibited the dominant peaks of ZnAl2O4 and V2O5. The crystallite size of the nanoparticles was estimated to be 16 nm. The sample was also studied using the Fourier transform infrared spectroscopy (FTIR), field-emission scanning electron microscopy (FESEM), and energy dispersive spectroscopy (EDS) to examine the functional groups morphology and elemental composition present in the composite nanoparticles. Further, these nanoparticles were employed in fabricating the prototype microstrip patch antenna to evaluate its characteristics. The fabricated antenna showed its return loss of -17.13 dB at a resonant frequency of 4.64 GHz.